1985
DOI: 10.4310/jdg/1214439718
|View full text |Cite
|
Sign up to set email alerts
|

Real Kaehler submanifolds and uniqueness of the Gauss map

Abstract: The main purpose of this paper is to answer the question: To what extent is a euclidean submanifold determined by its Gauss map? More precisely, let /,/: M" -> R n+P be two isometric immersions of a connected riemannian manifold whose Gauss maps into the Grassmannian G np are congruent. When are / and / congruent? Classical examples of isometric noncongruent deformations with the same Gauss map are the associated families of minimal surfaces in R 3 . They are a special case of associated families which can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 17 publications
0
74
0
Order By: Relevance
“…The following proposition is the indefinite version of a result due to Dajczer-Gromoll [4], which can be proved in the same way as in the positive definite case.…”
Section: Preliminariesmentioning
confidence: 60%
“…The following proposition is the indefinite version of a result due to Dajczer-Gromoll [4], which can be proved in the same way as in the positive definite case.…”
Section: Preliminariesmentioning
confidence: 60%
“…However, we recall that any minimal real Kähler submanifold f : M 2n → R N is the real part of a holomorphic complex submanifold g: M 2n → C N = R N ⊕ R N , f = Re g; cf. Theorem 1.11 in [DG1] and Remark 8 in [FHZ].…”
Section: Proof Of Theoremmentioning
confidence: 99%
“…The local classification for hypersurfaces without flat points was carried out in [3]. It was shown that they are abundant and can be parametrized by means of a pseudoholomorphic surface in S 2n (the Gauss image) and a smooth function over it.…”
Section: The Statementmentioning
confidence: 99%